The link between financial stress index and economic activity: prominent Granger causalities across frequencies in Luxembourg - Bahramian, Pejman; Saliminezhad, Andisheh; Aker, Sule (Emerald Group Publishing Ltd, 2021)
Purpose In spite of the certain risk imposed by financial stress on the real economy, the relationship between financial stress and economic activity is complicated and underresearched, meaning that important gaps still remain in the authors' understanding of this critical relationship. Therefore, the current study aims to answer the significant question regarding whether a stressful financial sector has predictive power on the real sector and vice versa. Hence, the study examines the causal interrelationship between financial stress index (FSI) and economic activity in Luxembourg as a sample country. Design/methodology/approach In this study, accompanying the time domain Granger causality framework of Hacker and Hatemi-J (2012), the authors utilize the spectral causality technique of Breitung and Candelon (2006), which is based on the study of Geweke (1982) and Hosoya (1991). This method enables the researcher to measure the degree of a particular variation in time series. Moreover, it allows considering the nonlinearities and causality cycles. The authors further apply the recent method of Farne and Montanari (2018) that is a bootstrap framework on Granger-causality spectra, which allows for disambiguation in causalities. Findings The time-domain approach finds evidence of bidirectional causation between the variables. However, the spectral causality results indicate the causal linkages between the series are only valid under the medium-run frequency. This study's findings emphasize covering the frequency causality to deliver a more comprehensive picture of the interrelationship between the variables. Originality/value There are many studies in this area that examine the nexus between financial stress and economic activity. However, the authors believe this paper is the first study in the context of Luxemburg. The authors focus on this country since its financial sector is designated as the most important pillar for the economy. Thus, a careful and reliable examination of the relationship between the financial sector and economic activity is likely to be of considerable interest to policymakers and researchers in this field.
Keywords: Frequency domain causality; Financial stress index; Economic growth; Luxembourg; C54; G28; O11